The trapper's bible : the most complete guide to trapping and hunting tips ever - Livingston, Eustace Hazard (Skyhorse Pub., 2012)
A collection of tips, tactics, and anecdotes from the finest trappers the United States has ever seen, The Trapper's Bible is an essential reference guide for hunters, trappers, and historians. Taken directly from some of the upmost authorities on the trapping profession, hundreds of photos and illustrations adorn this fascinating compendium. Broken up into sections, this volume details a wide variety of different traps and contains an extensive section outlining the behavior and nature of a long list of animals commonly hunted and trapped. The Trapper's Bible offers the best of the best -- an informative look into life as a trapper. From a complete listing of steel traps to constructing a variety of deadfalls, pens, traps, triggers, and snares, the collected sources take you through the ins and outs of trapping, including practical how-to instructions as well as personal stories and letters from real trappers.